New Zealand's agricultural trade approach after Cancun - Robert Thompson; Ralph Lattimore; Chris Nixon (New Zealand Institute of Economic Research (NZIER), 2003)
The mid-term review of the WTO Doha Round of trade negotiations held recently in Cancun was concluded in a premature fashion by the hosts. Participants were not moving forward towards a process that would see the talks move towards a final agreement in 2004. This was a disappointment for New Zealand because we rely strongly on the WTO multilateral framework to further liberalise world trade. This is especially so in agricultural products where it was hoped that after the modest beginnings of the Uruguay Round, signed in 1994, progress could be made more quickly. The stop/start negotiations of the Uruguay Round were not dissimilar. Cancun stumbled on the Singapore issues, and before agricultural proposals had been dealt with. This fortuitous situation provides an important opening for New Zealand agriculture but a great deal of work will need to be done. The other positive feature coming out of Cancun is that the slippage in timing is likely to be great (see below), so New Zealand has the time even with its modest resources, to influence the direction of the agricultural talks. NZIER hosted a Roundtable discussion on the opportunities and challenges that now confront New Zealand, yesterday in Wellington. Participants included representatives from private sector organisations, government ministries and research organisations. This short paper is a précis of the views expressed at that meeting and the valuable background material of the Washington based International Policy Council which Dr Thompson chairs. The discussion was aimed specifically at agricultural trade liberalisation efforts and focuses on the broad geo-political issues that are likely to be in play in the future.
Keywords: 330; Agraraußenhandel; Neuseeland